An Early Ethiopic Manuscript Fragment (Twelfth–Thirteenth Century) from the Monastery of St Antony (Egypt) - el-Antony, Fr. Maximous; Blid, Jesper; Butts, Aaron Michael (Aethiopica, 2017)
This article presents a single fragmentary folio that was recently uncovered in excavations at the Monastery of St Antony (Egypt). This folio was discovered in a secondary deposit below the foundations of a church which was in all likelihood constructed in the 1230s. A radiocarbon dating of the folio has returned a date of 1160–1265. Together, these two data make this fragmentary folio the earliest securely datable specimen of an Ethiopic manuscript. This find, thus, provides a new foundation for the analysis of the paleography of the earliest Ethiopic manuscripts, including the gospel manuscripts from Ǝnda Abba Gärima, which contain paleographic features that seem to predate this fragmentary folio. In addition, this find has implications for the regnant periodization of Ethiopic literature and more specifically the history of Ethiopic monastic literature, especially the Zena Abäw. Finally, this folio is among the earliest surviving Aethiopica for the entirety of Egypt and thus provides new information on the relationship between Ethiopic and Coptic Christianity.